THE PROBLEM OF INCREASING THE SPEED OF FREIGHT TRAINS - Melnechuk, V. O.; Pshinko, O. M.; Savchuk, O. M. (Science and Transport Progress, 2008)
In the paper a problem of increasing the traffic speed of fright trains is considered.